DAMPAK PENERAPAN EKONOMI KREATIF TERHADAP PEMULIHAN DAYA BELI PADA UMKM DI MASA TRANSISI PANDEMI COVID-19 - Ikhsanuddien, Yusril; Nuryana, Angga (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Current pandemic transition period is an opportunity for MSME to increase consumer purchasing power, and the creative economy may help MSME recover revenue since it is based on ideas and creativity, which can assist MSME in overcoming difficult conditions such as the COVID-19. This study aims to evaluate the impact of the creative economy on UMKM's selling power during the covid-19 transition phase. This study utilized a qualitative research methodology that incorporated both primary and secondary data sources, interview data collection procedures, and a literature review. Five informants were interviewed; all of them are micro, small, and medium-sized enterprise (MSME) actors who utilize the creative economy to operate their firms. The city of Tasikmalaya serves as the location of research. Several features of the creative economy can have a positive effect on the recovery of purchasing power throughout the transition period, as shown in the information collected.